First comparative analysis of complete chloroplast genomes among six Hedysarum (Fabaceae) species - Juramurodov, Inom; Makhmudjanov, Dilmurod; Yusupov, Ziyoviddin; Tojibaev, Komiljon (Frontiers in Plant Science, 2023)
Hedysarum is one of the largest genera in the Fabaceae family, mainly distributed in the Northern Hemisphere. Despite numerous molecular studies on the genus Hedysarum, there is still a lack of research aimed at defining the specific characteristics of the chloroplast genome (cp genome) of the genus. Furthermore, the interrelationships between sections in the genus have not yet been studied on the basis of the cp genome. In this study, comprehensive analyses of the complete cp genomes of six Hedysarum species, corresponding to sections Multicaulia, Hedysarum and Stracheya were conducted. The complete cp genomes of H. drobovii, H. flavescens, and H. lehmannianum were sequenced for this study. The cp genomes of six Hedysarum species showed high similarity with regard to genome size (except for H. taipeicum), gene sequences, gene classes, and the lacked IR region. The whole cp genomes of the six species were found to contain 110 genes ranging from 121,176 bp to 126,738 bp in length, including 76 protein-coding genes, 4 rRNA genes, and 30 tRNA genes. In addition, chloroplast SSRs and repetitive sequence regions were reported for each species. The six Hedysarum species shared seven common SSRs and exhibited fourteen unique SSRs. As well, three highly variable genes (clpP, accD, atpF) with high Pi values were detected among protein-coding genes. Furthermore, we conducted phylogenetic analyses using the complete cp genomes and 76 protein-coding genes of 14 legume species, including the seven Hedysarum species. The results showed that the Hedysarum species form a monophyletic clade closely related to the genera Onobrychis and Alhagi. Furthermore, both of our phylogenetic reconstructions showed that section Stracheya is more closely related to section Hedysarum than to section Multicaulia.